Understanding the employment impact of neuromyelitis optica spectrum disorder in the USA: Mixed methods - Mateen, Farrah J.; Trápaga Hacker, Cristina M. (Frontiers in Neurology, 2023)
Neuromyelitis optica spectrum disorder (NMOSD) is a rare and disabling neurological disorder, marked by recurrent attacks of the central nervous system. NMO has a high female predominance and disproportionately affects racial and ethnic groups who are under- and unemployed in the USA. Three focus groups, involving 20 working age adults with NMOSD in the USA, were convened via Zoom online, to discuss the topic of employment in NMOSD. Consolidated Criteria for Reporting Qualitative research (COREQ) were followed. Discussions were coded for major themes using an inductive approach. The following themes emerged: (1) Barriers due to NMOSD on employment including (i) visible and invisible symptoms, (ii) the burden of treatment, and (iii) time to diagnosis; (2) Mitigating factors when NMOSD affects employment; (3) Impact of COVID-19; (4) Impact on income; (5) Impact on new and future employment and higher education opportunities; and (6) Unmet needs that are pragmatically addressable, outside of major policy or scientific changes.